(untitled) (Modern education and development, 2025)
The rapid growth of digital data necessitates efficient methods for processing large volumes of information. Machine knowledge, an advanced approach that integrates artificial intelligence (AI), machine learning (ML), and knowledge representation techniques, plays a crucial role in this process. This paper explores various methodologies for handling vast amounts of information, highlighting their effectiveness, advantages, and limitations.